Nutritional status in pregnancy: Preliminary study. - Mendoza Arana, Pedro (2015)
We performed a cross-sectional study to estimate the prevalence of malnutrition instant pregnant in a poor urban area of Lima. The sample included 61 pregnant women and 75 women control over 15 group, not pregnant, apparently healthy. The prevalence of protein-energy malnutrition in pregnant women of 29.6% was found, using the criterion of percentage weight / size for gestational age according to the nomogram Rosso, and a prevalence of 26.7% in non-pregnant, and this difference was not statistically significant . It also reports a proportion of pregnant women under 20 years of 11.5% and 49.2% of pregnant women had at least one prenatal care. We conclude that the prevalence of malnutrition in pregnant women is high and would be related primarily to pre-gestational nutritional status.